2004
DOI: 10.1159/000076597
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Onset of Treatment or Increment in LT4 Dose in Screened Congenital Hypothyroidism: Which Was the More Important Factor for IQ at 7 Years?

Abstract: Objective: To determine between timing and LT4 dose which was the more important factor for IQ at 7 years in screened congenital hypothyroidism (CH). Methods: 131 children with CH born from 1979 to 1994 and 30 controls were studied. Mean age at recall: 22.8 ± 1.1 days. Mean initial LT4: 5.6 ± 0.1 µg/kg/day. Results: Optimal global IQ (GIQ; 119.0 ± 1.8) was obtained for a recall ≤15 days. Results for a recall after 3 weeks were lower (107.7 ± 2.4). The IQ of infants treated before 21 days (117.1 ± 1.2) was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
2
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 13 publications
2
17
2
9
Order By: Relevance
“…This is in accordance with the findings of other studies (22,28). This lack of association can be attributed to the early high-dose treatment regimen, which may eliminate the effects of initial dose or onset of treatment as reported by studies using either low dose (Ͻ10 g/kg/d) or late onset of treatment or both (11,29,30).…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with the findings of other studies (22,28). This lack of association can be attributed to the early high-dose treatment regimen, which may eliminate the effects of initial dose or onset of treatment as reported by studies using either low dose (Ͻ10 g/kg/d) or late onset of treatment or both (11,29,30).…”
Section: Discussionsupporting
confidence: 91%
“…The DQ scores for adaptive behavior, fine motor, gross motor, language, and personal-social behavior were comparable between the patients who began therapy ≤ 20 days after birth and those who began therapy > 20 days after birth (p > 0.05). The DQ scores for adaptive behavior, fine motor, gross motor, language, and personal-social behavior [23]. However, an Australian report showed that the mean full scale IQs were similar between infants who started treatment after 14 days of age and those who started before 14 days of age [24].…”
Section: Correlative Analysis Of Neurodevelopmental Outcomes In Ch Chmentioning
confidence: 99%
“…The initiation of treatment in the first two weeks of life gives the child a chance for normal intellectual and physical development [8][9][10]. In the most common primary hypothyroidism, levothyroxine preparations (L-T4) are considered to be the most effective.…”
Section: Treatment Of Congenital Hypothyroidismmentioning
confidence: 99%
“…Rozpoczęcie leczenia w ciągu pierwszych 2 tygodni życia daje dziecku szansę na prawidło-wy rozwój intelektualny i fizyczny [8][9][10]. W najczęściej występującej, pierwotnej niedoczynności tarczycy uważa się za najkorzystniejsze podawanie preparatów lewoskrętnej tyroksyny (L-T4).…”
Section: Leczenie Wrodzonej Niedoczynności Tarczycyunclassified